1999
DOI: 10.1037/0012-1649.35.3.701
|View full text |Cite
|
Sign up to set email alerts
|

What's in a smile?

Abstract: In positive social contexts, both adults and older infants show more Duchenne smiling (which involves high cheek raising) than non-Duchenne smiling (which does not). This study compared Duchenne and non-Duchenne smiles in early infancy for clues to their emotional significance. Infants (N = 13) from 1 to 6 months of age were videotaped weekly for 5 min in 208 face-to-face interactions with their mothers. Levels of Duchenne and non-Duchenne smiling were correlated within interactive sessions, and the 2 smiles h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 14 publications
(43 reference statements)
10
78
0
2
Order By: Relevance
“…As reported in other studies of mother-infant interaction (e.g., Malatesta & Haviland, 1982;Messinger, Fogel, & Dickson, 1999), infants' positive affect increased from 3 to 6 months. We also found indirect evidence that negative affect was decreasing.…”
Section: Discussionsupporting
confidence: 83%
“…As reported in other studies of mother-infant interaction (e.g., Malatesta & Haviland, 1982;Messinger, Fogel, & Dickson, 1999), infants' positive affect increased from 3 to 6 months. We also found indirect evidence that negative affect was decreasing.…”
Section: Discussionsupporting
confidence: 83%
“…lower than the average recognition rate) for expressions of fear, surprise, and disgust (see Table 3 for a summary of our design recommendations to enhance recognition of emotions by users). Furthermore, the expression of disgust is a noteworthy exception to the good performance of the "end of speech" condition: The temporal pattern also influenced the perceived intensity of emotions, but in a different way: the "during speech" condition resulted in higher perceived intensity, which can be attributed to the total duration of the facial expression -in the "during speech" condition the facial expression was twice as long as in all other conditions -and is consistent with existing literature suggesting that duration and intensity are correlated in the generation [23] and perception [25] of facial expressions. However, variations in the duration of facial expressions constitute a limitation of our study and would require a new experimental iteration in order to be better understood: in particular, we wonder whether they might introduce biases in the evaluation of realism since the correlation matrix showed that realism was strongly correlated to intensity of the stimuli.…”
Section: Discussionsupporting
confidence: 87%
“…Eye contact is a powerful social signal and plays a crucial role in regulating social interactions from the first months of life [17]. Before they are able to speak, infants and toddlers communicate with others using well-timed looks coordinated with gestures and vocalizations [26], [14]. Eye contact also plays a key role in joint attention, used to denote a class of behaviors in which children use gaze and gesture to spontaneously create or indicate a shared point of reference with another person [28].…”
Section: Introductionmentioning
confidence: 99%